(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
Presentation in oral format carried out by me with the characteristic of a virtual exhibition, at the MEETING OF SCENOGRAPHIC ARTS & Seminar on Scenographic Pedagogies and Poetics, held in August 2023. I describe in this lecture about my research "The creation of costumes for Rancho Ameno Resedá, through the analysis of watercolors created by Amaro Amaral in 1913", of which I have also published a book about the theme. I approach this narrative with my place of speech supported by my trajectory as a researcher, who has explored fashion, the costumes of different shows (including carnival) and I have been observing these languages, considering them practices similar to design – as a field of production. This is all available to read at the link https://drive.google.com/file/d/1UyXaQmr8X0Ck1v3a9NRtm1MACa9LaU3o/view, in a chapter titled “Particular Forms of Design. What is it, why and how?”, published in this book.